Analisis Pesan Dakwah Streamer Ustaz Abi Azkakia dalam Channel YouTube M-Key Gaming Game Mobile Legends pada Episode Bane Hijrah - Rizki; Kusnadi; Anang Walian (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
A da'wah message is a message containing Islamic da'wah material that is conveyed to the recipient of the da'wah. In the era of globalization, technology is developing rapidly. The method of preaching has also been carried out by utilizing modern technology, namely through online games. Ustaz Abi Azkakia has his own uniqueness which makes him different from Ustaz in general, namely because he preaches while playing Mobile Legends, the most popular game among children today. The research entitled "Analysis of Streamer Ustaz Abi Azkakia's Da'wah Message on the M-Key Gaming Game Mobile Legends YouTube Channel in the Bane Hijrah Episode" is qualitative research using content analysis research techniques. This research aims to find out what the preaching messages of streamer Ustaz Abi Azkakia are on the YouTube channel m-key gaming game mobile legends in the Bane Hijrah episode. Data collection methods use documentation, observation and literature study methods. The data in this research was taken from a video on the M-Key Gaming Game Mobile Legends YouTube channel in the episode "Bane Hijrah" by streamer Ustaz Abi Azkakia. The results of this research are that there are a total of 9 preaching messages on the M-Key Gaming Game Mobile Legends YouTube channel in the episode "Bane Hijrah". Of the 9 da'wah messages, there are 3 messages of moral da'wah, 4 messages of sharia da'wah and 2 messages of religious da'wah.